2010
DOI: 10.1007/s00436-010-2022-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a combination of imidacloprid 10%/moxidectin 2.5% spot-on (Advocate® for dogs) in the prevention of canine spirocercosis (Spirocerca lupi)

Abstract: The nematode Spirocerca lupi is a major canine parasite in warm regions of the world, classically causing parasitic nodules in the esophagus, aortic aneurysms, and spondylitis. This study evaluated the preventive efficacy of monthly treatment with imidacloprid 10%/moxidectin 2.5% spot-on (Advocate® for dogs) administered over a period of 9 months in young dogs naturally exposed to S. lupi on Réunion island. One hundred and twelve puppies, aged from 2.0 to 4.0 months and with a negative spirocerca fecal examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Some literature resources claim disophenol to be the only confirmed adulticide drug, but it does not affect juvenile worms and is not available on the market (Lobetti 2013). Other sources claim that macrocyclic lactones are an effective treatment for benign esophageal alterations caused by Spirocerca lupi (Berry 2000, Kelly et al 2008, Lobetti 2012, Austin et al 2013), while effective prevention is possible with avermectins, milbemycin and moxidectin , Kelly et al 2008, Kok et al 2010, 2011, Le Sueur et al 2010, Nolan et al 2012). In our experience, doramectin-treated patients become symptomfree, but use of the drug is greatly hindered by off-label application and the risk of complications.…”
Section: S105mentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature resources claim disophenol to be the only confirmed adulticide drug, but it does not affect juvenile worms and is not available on the market (Lobetti 2013). Other sources claim that macrocyclic lactones are an effective treatment for benign esophageal alterations caused by Spirocerca lupi (Berry 2000, Kelly et al 2008, Lobetti 2012, Austin et al 2013), while effective prevention is possible with avermectins, milbemycin and moxidectin , Kelly et al 2008, Kok et al 2010, 2011, Le Sueur et al 2010, Nolan et al 2012). In our experience, doramectin-treated patients become symptomfree, but use of the drug is greatly hindered by off-label application and the risk of complications.…”
Section: S105mentioning
confidence: 99%
“…The toxicity depends on the mutation of the MDR-1 Δ gene and the expression of protective glycoprotein P (Lobetti 2013). Milbemycin oxime, applied at 0.5 mg/kg for 28 days (Beugnet et al 2016, Kok et al 2010, 2011, or spot-ons containing a combination of imidacloprid and moxidectin are both confirmed as being suitable for spirocercosis prevention (Austin et al 2013, Le Sueur et al 2010. Although the esophageal granulomas caused by Spirocerca lupi can be successfully treated with doramectin, sarcomas require surgical and oncological treatment (Willard 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore control of Spirocerca lupi in the final host by medical prevention or therapy seems to be the only viable option. Most studies in which macrocyclic lactones were tested for efficacy against S. lupi focused on therapeutic efficacy (Berry 2000;Lavy et al 2002;Kelly et al 2008), and although some treatment regimens have indicated promising preventative efficacy (Lavy et al 2003;Kok et al 2010;Le Sueur et al 2010), this issue remains largely unresolved. The present study was designed to evaluate both preventative and therapeutic efficacy in experimentally infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…The adequacy of infection in the control group enabled a valid comparison of treated groups to the control group. The use of oesophagoscopy to detect oesophageal nodules associated with S. lupi infections is a standard diagnostic procedure (Mazaki-Tovi et al 2002) and has been used often in studies to determine the efficacy of therapeutic procedures in the treatment of progressed spirocercosis (Lavy et al 2003;Kelly et al 2008;Le Sueur et al 2010;Lobetti 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation